2020
DOI: 10.3389/fmicb.2020.01735
|View full text |Cite
|
Sign up to set email alerts
|

Great Tit (Parus major) Uropygial Gland Microbiomes and Their Potential Defensive Roles

Abstract: The uropygial gland (preen gland) of birds plays an important role in maintaining feather integrity and hygiene. Although a few studies have demonstrated potential defensive roles of bacteria residing within these glands, the diversity and functions of the uropygial gland microbiota are largely unknown. Therefore, we investigated the microbiota of great tit ( Parus major ) uropygial glands through both isolation of bacteria (culture-dependent) and 16S rRNA amplicon sequencing (culture-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 79 publications
0
15
0
Order By: Relevance
“…In the most robust study to date (Goodenough et al 2017), no skin-related bacterial taxa were found to be dominant or differentially prevalent in our study. Similarly, taxa associated with uropygial gland secretions (that often are later identified on bird skin) in the closely related great tit do not overlap convincingly with our ASVs (Bodawatta et al 2020a). More work is needed to understand the variation of bird microbiomes across different body regions and how cross-contamination could confound results in studies like ours.…”
Section: Discussionmentioning
confidence: 55%
“…In the most robust study to date (Goodenough et al 2017), no skin-related bacterial taxa were found to be dominant or differentially prevalent in our study. Similarly, taxa associated with uropygial gland secretions (that often are later identified on bird skin) in the closely related great tit do not overlap convincingly with our ASVs (Bodawatta et al 2020a). More work is needed to understand the variation of bird microbiomes across different body regions and how cross-contamination could confound results in studies like ours.…”
Section: Discussionmentioning
confidence: 55%
“…More likely is that the microbes originating from parents shape the dynamics in eggshell microbial community during incubation [10,11,43,44]. For instance, we found noticeable increase in the proportion of Firmicutes on the eggshell and Firmicutes include species of microbes present in uropygial gland [45] gastrointestinal tract [38,46,47], or feathers [48]. It is plausible that the microbes originating from parents, either through contact with cloaca (when laying) or with uropygial gland and feathers (during incubation), are transferred once or continuously to the eggshell and shape the dynamics and phylogenetic turnover in eggshell microbial community.…”
Section: Composition Of Microbial Communitiesmentioning
confidence: 73%
“…These results suggest a possible interaction between infection and microbiota. Some microorganisms have been identified as potential symbionts in the uropygial gland ( 41 ). Based on functional predictions using 16S rRNA sequences, uropygial gland bacteria were suggested to produce metabolites with antimicrobial properties, such as terpenes ( 41 ).…”
Section: The Gut Microbiota and Plasmodium Infectionmentioning
confidence: 99%